Study on Attenuating Efficiency of a Dye Pollutant by Physico-chemical Adsorption - Mohan D.; Singh V.N.; Shekhar H. (My University, 2025)
With a view to provide optimum conditions for the maximum removal of dye pollutant (Lissamine red) from wastewater in a treatment plant, the adsorption ability of coal has been studied at different adsorbate concentrations, contact times temperatures and pH of the solution. The data of the adsorbate - adsorbent systems, thus obtained suggest that the lower concentration higher pH and lower temperature of the system have been in good favour of the removal of Lissamine red. The dynamics of adsorbate (Lissamine red) transport from bulk to solid surface has been studied with the help of the adsorption of the dye as well as diffusion of dye within the pores of coal.